The Influence of Ice Accretion on the Thermodynamic Performance of a Scientific Balloon: A Simulation Study - Qiang Liu; Lan He; Yanchu Yang; Kaibin Zhao; Tao Li; Rongchen Zhu; Yanqing Wang (Aerospace)
A scientific balloon is the ideal platform for carrying out long-duration missions for scientific research in the stratosphere. However, when a scientific balloon ascends through icy clouds and reaches supercooled droplets, there is a risk of ice accretion on the balloon’s surface. Ice accretion on the balloon can threaten flight safety and the accomplishment of missions and can even result in disastrous accidents. A comprehensive simulation platform was developed to simulate the influence of ice accretion on the thermodynamic performance of a scientific balloon to provide quantitative data support for balloon design and flight operations. The simulation platform consisted of two parts: one based on ANSYS software to solve the accretion model and the other a program developed with MATLAB software to solve the thermodynamic model. The results suggest that, in certain cloud environments, there is a risk of ice accretion on a balloon’s surface; the extra ice mass added to the balloon may prevent it from ascending through icy clouds and instead keep it floating at the base of these clouds.